1994
DOI: 10.1289/ehp.9410264
|View full text |Cite
|
Sign up to set email alerts
|

Carcinogenic and Cocarcinogenic Effects of Radon and Radon Daughters in Rats.

Abstract: It has been previously established that lung cancer could be induced in rats by exposure to radon and radon daughters. Although the oat-cell carcinomas that are common in humans were not found in rats, other histological types of lung carcinomas, especially squamous cell carcinomas and primitive lung adenocarcinomas, were similar to those observed in humans. A dose-effect relationship was established for cumulative doses varying from 25 to 3000 working-level-months (WLM), which was similar for medium and high … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
0
4

Year Published

1994
1994
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(30 citation statements)
references
References 32 publications
3
23
0
4
Order By: Relevance
“…La différentia-tion préférentielle des cancers pulmonaires induits par l'ozone vers le type épidermoïde est à noter. Une telle tendance a déjà été rapportée dans le cas d'effets cocancérogènes observés après exposition cornbinée au radon et à la fumée de ciga-rettes ou de certains de ses composants comme la 5-6 benzoflavone (bNF) chez le rat [12,13]. Le fait que des raccourci sssements significatifs des temps de survie n'aient été observés, ni chez les animaux exposés à l'ozone seul, ni chez les animaux exposés à l'ozone après inhalation préalable de radon, peut laisser supposer que l'effet cocancérogène observé n'est pas un véritable effet synergique.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…La différentia-tion préférentielle des cancers pulmonaires induits par l'ozone vers le type épidermoïde est à noter. Une telle tendance a déjà été rapportée dans le cas d'effets cocancérogènes observés après exposition cornbinée au radon et à la fumée de ciga-rettes ou de certains de ses composants comme la 5-6 benzoflavone (bNF) chez le rat [12,13]. Le fait que des raccourci sssements significatifs des temps de survie n'aient été observés, ni chez les animaux exposés à l'ozone seul, ni chez les animaux exposés à l'ozone après inhalation préalable de radon, peut laisser supposer que l'effet cocancérogène observé n'est pas un véritable effet synergique.…”
Section: Discussionunclassified
“…Le fait que des raccourci sssements significatifs des temps de survie n'aient été observés, ni chez les animaux exposés à l'ozone seul, ni chez les animaux exposés à l'ozone après inhalation préalable de radon, peut laisser supposer que l'effet cocancérogène observé n'est pas un véritable effet synergique. Toutefois, au vu des résultats antérieurs obtenus en utilisant ce modèle de cocancéroge-nèse, l'ozone est le seul aérocontaminant identifié avec la fumée de tabac [12,14) capable d'induire un doublement de l'incidence des tumeurs pulmonaires après exposition préalable au radon.…”
Section: Discussionunclassified
“…It has been demonstrated that exposure to radon can induce lung tumors and other cancers in experimental animals [43]. Also, a radon dose-related carcinogenicity has been shown through epidemiologic studies of miners and case-control studies in the general population [44][45][46][47].…”
Section: Case Studiesmentioning
confidence: 99%
“…poprzez reakcję radiolizy inicjuje powstanie wolnych rodników, w tym najbardziej reaktywnego rodnika hydroksylowego (6)(7)(8). Zniszczenia, których źródłem są RFT, mogą z kolei inicjować procesy kancerogenne (8)(9)(10). Ze wspomnianego wyżej wolnorodnikowego modelu oddziaływania PEM wynika więc możliwość zmiany skutków jakościowych i ilościowych działania promieniowania jonizującego.…”
Section: Wstępunclassified